The Role of the Principal in Curriculum Development at Ar Roudhoh Islamic Middle School - Ira Raudah; Hinggil Permana; Ceceng Syarif Husein (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore the role of school principals in curriculum development at SMP Islam Ar Roudhoh. Utilizing a qualitative approach, data were collected through in-depth interviews and observations involving the principal and several teachers. The findings reveal that effective leadership, characterized by participatory practices, significantly enhances teacher collaboration and curriculum innovation. The principal's support in integrating technology into the curriculum further contributes to improved educational quality. The study concludes that a principal's active involvement in curriculum development not only fosters a positive school environment but also addresses the challenges teachers face, ultimately leading to better educational outcomes. These insights underscore the importance of strong leadership in educational settings and provide a framework for enhancing curriculum practices in Islamic schools.